Central Retinal Vein Occlusion in young with Hyperhomocysteinemia – A Case Report and Review of Literature - Ifsa Sami; Reena Sharma; Ahmad Husain; Ravi Ranjan (Delhi Journal of Ophthalmology)
We present a case of unilateral non-ischemic CRVO in a 22 year male without hypertension, diabetes and open angle glaucoma. Laboratory tests including complete coagulation profile and thrombotic workup were negative, except for raised serum homocysteine level(23.03 µmol/L). The patient was given vitamin supplements for 8 weeks to control homocysteine levels and a single intravitreal bevacizumab injection was given to treat macular edema. The vision and macular thickness improved to normal at 8 weeks, with no recurrence or new cardiovascular complications over a follow-up of one year. We also reviewed the literature and found hyperhomocysteinemia to be a important risk factor for CRVO in the young, and vitamin supplements help in quicker recovery and can prevent recurrence.